Giving Assimilation for Prisoners in Gorontalo Penitentiary During the Covid-19 Pandemic - Usman, Rusli; Darmawati, Darmawati; Nur, Rafika (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2023)
The Covid-19 pandemic in early 2020 was a problem in Indonesia. To protect prisoners during a pandemic, it is necessary to make regulations related to assimilation programs for prisoners. This research combines normative and empirical research by studying norms relating to the terms and procedures for granting assimilation to inmates during a pandemic and looking directly at the implementation of assimilation during a pandemic in Class IIA Gorontalo Prison. The results of the study show that the assimilation program for prisoners is regulated in two ministerial regulations in the field of Law and Human Rights. It was found that 193 prisoners receiving the assimilation program in 2020, 100 people in 2021, and 77 people in 2022. Obstacles faced by Class IIA Gorontalo Prison in implementing the granting of assimilation and integration rights are internal constraints related to clients, human resources, social assistants and prison officers, as well as the implementation system. External barriers are related to the culture of the Gorontalo people who still tend to have a negative stigma against convicts and choose to give social punishment by staying away from convicts because they are considered dangerous people. ___ References Books with an author: Darmawati. (2021). Dasar-Dasar Penologi dan Pemasyarakatan. Yogyakarta: Deepublish. Mahmutarom HR, (2010). Rekonstruksi Konsep Keadilan Studi tentang Perlindungan Korban Tindak Pidana dalam Hukum Positif, Hukum Islam, Konstruksi Masyarakat dan Instrumen Internasional. Semarang: Badan Penerbit Universitas Diponegoro. Mukti Fajar, N. D., and Achmad, Y. (2010). Dualisme Penelitian Hukum: Normatif & Empiris. Yogyakarta: Pustaka Pelajar. Napitupulu, R. A. (2020). Tinjauan Yuridis Mengenai Pemberian Hak Asimilasi Terhadap Narapidana dalam Permenkumham Nomor 10 Tahun 2020 Tentang Syarat Pemberian Asimilasi dan Hak Integrasi Bagi Narapidana dan Anak dalam Rangka Pencegahan dan Penanggulangan Penyebaran Covid-19 dan Kaitannya dengan Hak Asasi Manusia, Medan: Universitas Sumatera Utara. Nur, Rafika. (2020). Sanksi Tindakan dalam SPPA. Parepare: Sampan Institute. Pasamai, S. (2013). Metodologi Penelitian dan Penulisan Karya Ilmiah Hukum. Makassar: Arus Timur. Rahardjo, Satjipto. (1980). Hukum dan Masyarakat. Bandung: Angkasa. Sholehuddin M. (2003), Sistem Sanksi dalam Hukum Pidana. Jakarta: Rajawali Press. Article journal: Hermawan, R. A., Sapsudin, A., Tonni, M., and Kertawijaya, S. (2021). Analisis Hukum terhadap Asimilasi sebagai Hak Narapidana Ditinjau dari Undang-Undang Nomor 12 Tahun 1995 tentang Pemasyarakatan (Studi Kasus di Lembaga Pemasyarakatan Kelas IIB Banjar). Case Law, 2(2), 117-139. Jufri, E. A., and Anisariza, N. U. (2017). Pelaksanaan Asimilasi Narapidana di Lembaga Pemasyarakatan Terbuka Jakarta. ADIL: Jurnal Hukum, 8(1), 1-26. Koesnindary, S. D., Wahyudi, S., and Hendriana, R. (2021). Kebijakan Pembebasan Narapidana melalui Pemberian Asimilasi dalam Rangka Pencegahan Penyebaran Covid-19 di Lembaga Pemasyarakatan. Soedirman Law Review, 3(4), 646-663. Kurnianingrum, T. P. (2020). Kontroversi Pembebasan Narapidana di Tengah Pandemi Covid-19, Majalah Info Singkat, 12(8), 1-6. Poernomo, A. A. (2021). Disparitas Norma Pengaturan Pemberian Asimilasi, Pembebasan Bersyarat, Cuti Menjelang Bebas dan Cuti Bersyarat bagi Narapidana Tindak Pidana Narkotika pada Masa Pandemi Ditinjau dalam Perspektif Hierarki Peraturan Perundang-undangan. Jurnal Surya Kencana Dua: Dinamika Masalah Hukum dan Keadilan 8(1), 18-46. Surahmat, A., Dida, S., and Zubair, F. (2021). Analysis of the Government’s Crisis Communication Strategy Discourse to Defend Covid-19. Jurnal Komunikasi, 13(1), 36-53. Tantaru, F., Toule, E. R. M., and Ubwarin, E. (2021). Kajian Sosio-Yuridis Pembebasan Bersyarat dan Pemberian Asimilasi bagi Narapidana pada Masa Pandemi Covid-19 Ditinjau dari Perspektif Tujuan Pemidanaan. SANISA: Jurnal Kreativitas Mahasiswa Hukum, 1(1), 34-41.